Die Konstitusionele Hof se kultuurdiversiteitsopdrag aan die onderwys: Aanloklike bestemming anderkant n ongekaarte mynveld - Beckmann, Johannes Lodewyk (Suid-Afrikaanse Akademie vir Wetenskap en Kuns, 2017)
Culture and education are inextricably linked and education is one of the spheres in which an individual person or a collective may practise their closely-related rights to culture and freedom of expression. Different role players in education all have cultural rights and culture can have a beneficial or negative effect on the functioning of an educational institution and, consequently, on the realisation of cultural and educational rights. Because culture is an emotional issue linked to a person's concept of self-worth and may be misused to discriminate against people, members of a school community could easily feel that their cultural rights are threatened and culture-based conflict often ensues. A culturally homogeneous country is not as prone to endemic cultural conflict as a culturally deeply diverse country like South Africa. In South Africa, cultural rights and the expression and practice thereof are regulated by constitutional and other laws designed to ensure harmony in this regard. Nevertheless, cultural conflict often arises in South African schools and is sometimes even escalated to the courts. The functioning of schools is sometimes disrupted by culture-based conflict, of which the recent protests about the regulation of girls' hairstyles in some schools is an apt example.
Keywords: Cultural imperative; Cultural norms; Cultural pressure on decisions; Culture, Diversiteit; Diversity; Kulturele druk op besluite; Kulturele imperatief; Kulturele norme; Kultuur; Kwesbare groepe; Spanningsveld tussen die reg en kultuur; Tension between the law and culture; Tradisionele Afrika-kultuur; Traditional African culture; Ubuntu; Vulnerable groups; Western-positivist culture and Westers-positivistiese kultuur